Transmission of whole body vibration to the lower body in static and dynamic half-squat exercises (2016)
Whole body vibration (WBV) is used as a training method but its physical risk is not yet clear. Hence, the aim of this study is to assess the exposure to WBV by a measure of acceleration at the lower limb under dynamic and static postural conditions. The hypothesis of this paper is that this assessment is influenced by the frequency, position, and movement of the body. Fifteen healthy males are exposed to vertical sinusoidal vibration at different frequencies (20–60 Hz), while adopting three different static postures (knee extension angle: 180°, 120° and 90°) or performing a dynamic half-squat exercise. Accelerations at input source and at three joints of the lower limb (ankle, knee, and hip) are measured using skin-mounted accelerometers. Acceleration values (g) in static conditions show a decrease in the vibrational dose when it is measured at a more proximal location in the lower extremity. The results of the performed statistical test show statistically significant differences (p < 0.05) in the transmissibility values caused by the frequency, the position, and to the presence of the movement and its direction at the different conditions. The results confirm the initial hypothesis and justify the importance of a vibration assessment in dynamic conditions.